Effect Of pH, Temperature And Metal Ions On Amylase Activity From Bacillus Subtilis KCX 006 - K. AMUTHA,; K. JAYA PRIYA, (International Journal of Pharma and Bio Sciences, 2011)
Under different growth conditions such as pH, temperature and metal ions, Bacillus subtilis KCX006 was tested for amylase production and kinetic properties of amylase was determined. The enzyme activity was more in the stationary phase and the value was 21.78 U/mL (at 30 h) and protein content was 0.303 mg/mL. The maximum amylase activity (38 U/mL) was also found at stationary phase when the culture was grown at 37°C. The enzyme was purified to homogeneity with an overall recovery of 24.2% and specific activity of 4133 U/mg. Either acidic or alkaline condition significantly affected the growth and enzyme production. Enzyme activity was more in reaction mixture containing NiCl2 and its residual activity was found to be 117.5%. These results suggest possible application in food and detergent industries where moderate pH and temperature are employed.